2009
DOI: 10.1093/geront/gnp127
|View full text |Cite
|
Sign up to set email alerts
|

Ten Years Down the Road: Predictors of Driving Cessation

Abstract: These results underscore the importance of cognitive speed of processing to the maintenance of driving. Brief cognitive assessment can be conducted in the field to potentially identify older adults at increased risk for driving cessation. Further research is needed to determine the costs and potential benefits of such screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 41 publications
3
67
2
Order By: Relevance
“…Reduced speed of visual processing/attention (measured with UFOV score) was an independent risk factor in line with studies of driving cessation in aging. 29,30 The UPDRS-ADL score (risk factor for "ex-driver" status in a crosssectional study 31 ) and the daily total levodopa equivalent amount were independent risk factors of future driving cessation in the multivariate model suggesting that these measures better predict future functional impairment compared to the motor UPDRS score in the medicated ("on") phase.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced speed of visual processing/attention (measured with UFOV score) was an independent risk factor in line with studies of driving cessation in aging. 29,30 The UPDRS-ADL score (risk factor for "ex-driver" status in a crosssectional study 31 ) and the daily total levodopa equivalent amount were independent risk factors of future driving cessation in the multivariate model suggesting that these measures better predict future functional impairment compared to the motor UPDRS score in the medicated ("on") phase.…”
Section: Discussionmentioning
confidence: 99%
“…Just over one half (140 of 263, 53 per cent) of the current drivers reported that they felt that their cataract had affected their driving, including reduced confidence (53), reduced number of hours or distance driven (41), reduced speed compared to traffic flow (26), dependency on someone else to drive around (eight), avoidance of driving in rain (36), at night (85), in traffic (15), unfamiliar areas (28) or long distances (20), specific visual disturbances (36) including blur, glare, refractive change and other miscellaneous impacts (nine). Total weekly driving exposure varied greatly among participants.…”
Section: Self-reported Driving Difficulty and Exposurementioning
confidence: 99%
“…Calculations were based on cognitive impairment as the exposure variable of primary interest, as cognitive impairment is consistently reported to be a strong predictor of crash involvement and driving cessation in older adults (Edwards et al 2010). The incidence of mild cognitive impairment in older adults is about 5 per 100 person-years (Wouters et al 2010), the incidence of crashes in older adult drivers is about 5 per 100 person-years (Staplin et al 2003), and the risk ratio of crash involvement associated with mild cognitive impairment is reported to be 4.2 (Wadley et al 2009).…”
Section: Sample Size Estimation and Statistical Analysismentioning
confidence: 99%